Association of Haemostasis Activation Markers with Thrombophilia and Venous Thromboembolism - Vižintin-Cuderman, Tjaša; Božič-Mijovski, Mojca; Antović, Aleksandra; Peternel, Polona; Kozak, Matija; Stegnar, Mojca (IntechOpen, 2011)
None